2014
DOI: 10.1190/geo2014-0001.1
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeophysical investigations in the western and north-central Okavango Delta (Botswana) based on helicopter and ground-based transient electromagnetic data and electrical resistance tomography

Abstract: The Okavango Delta is a huge alluvial megafan in northwestern Botswana. Despite numerous geologic, geochemical, geophysical, and hydrologic investigations over the past half-century, the sedimentary units underlying the delta are largely unknown. To address this issue, helicopter transient electromagnetic data (HTEM) have been collected across the entire delta and coincident ground-based electrical resistance tomographic (ERT) and transient electromagnetic (TEM) data have been acquired at two locations, one al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…For example, in transitional coastal environments, AEM data have been used to map saltwater intrusion at scale of over tens to hundreds of square kilometers to study processes where fresh and saline surface waters mix with groundwater [Fitterman and Deszcz-Pan, 1998;Viezzoli et al, 2010]. Similar applications of AEM to inland environments revealed the presence of saline sediments in an aquifer system related to a paleo-Okavango Megafan [Meier et al, 2014]. Slater et al [2010] combined waterborne ERT/IP imaging with FO-DTS to investigate groundwater-surface water interaction along~3 km reach of the Columbia River, Washington (Figure 4).…”
Section: Groundwater/surface Water Interactionmentioning
confidence: 99%
“…For example, in transitional coastal environments, AEM data have been used to map saltwater intrusion at scale of over tens to hundreds of square kilometers to study processes where fresh and saline surface waters mix with groundwater [Fitterman and Deszcz-Pan, 1998;Viezzoli et al, 2010]. Similar applications of AEM to inland environments revealed the presence of saline sediments in an aquifer system related to a paleo-Okavango Megafan [Meier et al, 2014]. Slater et al [2010] combined waterborne ERT/IP imaging with FO-DTS to investigate groundwater-surface water interaction along~3 km reach of the Columbia River, Washington (Figure 4).…”
Section: Groundwater/surface Water Interactionmentioning
confidence: 99%
“…The structural framework of the Okavango Basin that is characterized by ongoing neo‐tectonic activity (Cooke, 1980; Gumbricht et al., 2001; Haddon, 2005; McCarthy, Green & Franey, 1993; McFarlane & Eckardt, 2007; Shaw, 1985) is well‐defined by satellite and aerial imaging (Hutchins, Hutton, Hutton, Jones, & Loenhert, 1976; Mallick, Habgood, & Skinner, 1981; McCarthy, 2013; McFarlane & Eckardt, 2007), and aeromagnetic and gravity surveys (Campbell, Johnson, Bakaya, Kumar, & Nsatsi, 2006; Kinabo et al., 2008; Meier et al., 2014; Modisi et al., 2000; Podgorski et al., 2013). A time frame of formation and evolution of accommodation space, on the other hand, is poorly constrained (Haddon, 2005; Nash & Eckardt, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Gabriel et al () used a combination of seismic, gravity and electrical methods to delineate extent of subglacial valleys and impacts of salt intrusion on the groundwater reservoirs. A number of other studies have shown the strength of multidimensional and multiscale geophysical applications to flow path delineation (e.g., McClymont et al ; Cassidy et al ; Meier et al ), contaminant transport and fate (e.g., Atekwana and Atekwana ; Konstantaki et al ), and karst characterization (e.g., Martínez‐Moreno et al ). While these previous studies demonstrate the capacity of geophysical techniques to understand various hydrogeological and geological problems, few have shown how an integrated, multidisciplinary and multiscaled approach can generate a robust conceptualization of a heterogeneous sedimentary bedrock environment, exhibiting multiple geologic unconformities with contrasting sedimentary rock types and characteristics, with varying hydrological impacts associated with dense nonaqueous phase liquid (DNAPL) migration and source evolution.…”
Section: Introductionmentioning
confidence: 99%